(3JbQjQGJ aj GdCUhds - (3Bd TOjO, GdMSjfj, GdcGXej, YHO GdQShd Hf eMeO Ydj Hf YHO GdYXje, J (B1330 (3g`s
(3ChdgG (B:s
(3GdebUO GdSGOS aj UdGI GdeSGaQ hJfbjM GdHMK jJe HQSe eHGMK GdChd dG ETcGd aj hLhH GdbUQ(B...s
(3BNQgG (B:s
(3aEf LYd GdMO Hjf GdLHdjf EfeG jJe dh cGf JbQjHG ceG gh hGVM dCf GdJMOjO GdJMbjbj EfeG jJe dh jPQY Hjfs
(3JHUQI GdYfhGf (B:s
(3JbQjQGJ GdTjN eMeO Ydj GdcGXejs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: (3L(B2(3, U(B142s
(3eYLe GdeDdajf(B: (3L(B2(3, U(B142s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis